2015
DOI: 10.17987/icfj.v1i4.45
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve syndrome and fibrillinopathies: potential impact on clinical approach

Abstract: Bicuspid aortic valve (BAV) is a common heterogeneous disorder whose natural history is determined by hemodynamic<br />valvular impairment and/or increased prevalence of aortic abnormalities ranging from dilatation to aneurysm and dissection.<br />BAV-related aortopathy is frequently associated with relevant aortic pathologic changes leading to structural alterations,<br />characteristic degenerative lesions and histological changes of the aorta very similar to those identified and described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…For example, in contrast to the Olmsted county study, in which abnormal auscultation was the most common clinical condition (71%) associated with the first clue of initial diagnosis,20) the wide clinical application and availability of routine echocardiography in Korea can reveal different clinical situations associated with the first diagnosis of BAV. On the other hand, focused screening due to family history of BAV or congenital heart disease was conducted only in 3 patients in our cohort, while previous Western studies reported that familial clustering was involved in 20%-30% of isolated BAV cases21) and that the concordance among first-degree relatives of BAV patients was 6.4% 22). Therefore, our results raised the question of whether we provide appropriate patient education for screening of BAV during routine practice at our institution.…”
Section: Discussionmentioning
confidence: 71%
“…For example, in contrast to the Olmsted county study, in which abnormal auscultation was the most common clinical condition (71%) associated with the first clue of initial diagnosis,20) the wide clinical application and availability of routine echocardiography in Korea can reveal different clinical situations associated with the first diagnosis of BAV. On the other hand, focused screening due to family history of BAV or congenital heart disease was conducted only in 3 patients in our cohort, while previous Western studies reported that familial clustering was involved in 20%-30% of isolated BAV cases21) and that the concordance among first-degree relatives of BAV patients was 6.4% 22). Therefore, our results raised the question of whether we provide appropriate patient education for screening of BAV during routine practice at our institution.…”
Section: Discussionmentioning
confidence: 71%
“…A combination of genetic, flow and environmental factors in the individual patient is probably responsible for AscAA formation [29]. The fact that microanatomy in the descending aorta (AoIMT) did not differ between BAV and TAV does not exclude differences in aortic function, or inherent tissue weakness as the etiology of BAV aortopathy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BAV has been described as an isolated trait or associated with other clinical manifestations in syndromic conditions [familial thoracic aortic aneurysm and dissection, Marfan syndrome (MFS), Loeys-Dietz syndrome, Andersen syndrome, Turner syndrome, William Beuren syndrome, Bosley-Salih-Alorainy syndrome, and Athabascan Brainstem Dysgenesis syndrome] [ 5 , 7 , 8 ]. Identification of a syndromic condition in a BAV patient is clinically relevant in order to personalize indication to aortic surgery [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different genes with divergent inheritance pattern have been described to be associated with BAV [ 6 ]. NOTCH1 (9q34.3, OMIM 190198), a transmembrane receptor involved in signaling pathways regulating cell fate and cardiovascular development processes, represents the main gene demonstrated to be associated with BAV in both familial and sporadic forms [ 7 , 11 , 12 ]. Mutations in NOTCH1 signaling genes have been associated with a wide spectrum of congenital heart defects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation